PROTECTIVE EFFECT OF SSANGHWA-TANG FERMENTED BY LACTOBACILLUS FERMENTUM AGAINST CARBON TETRACHLORIDE-INDUCED ACUTE HEPATOTOXICITY IN RATS - Eum, Hyun-Ae; Lee, Ji-Hye; Yang, Min-Cheol; Shim, Ki Shuk; Lee, Jae-Hoon; Ma, Jin Yeul (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
Ssanghwa-tang (SHT) is traditional herbal medicine formula that has been used for the development of physical strength, relief of pain, and the reduction of fatigue. In this study, we fermented SHT with Lactobacillus fermentum (L. fermentum), Lactobacillus gasseri (L.gasseri), or Lactobacillus casei (L.casei) to compare the hepatoprotective effects of SHT with fermented SHT against carbon tetrachloride (CCl4)-induced liver injury. Rats were given CCl4 (1 ml/kg, 50% CCl4 in olive oil) intraperitoneally and either SHT or fermented SHTs (15 ml/kg) was administered 30 min before CCl4. At 24 h after CCl4 injection, the levels of transaminases in the serum were markedly increased. These increases were significantly attenuated by either SHT + L. fermentum or SHT+ L.gasseri. However, SHT and SHT + L.casei showed slightly suppression of the increase of transaminases. The liver histological changes were diminished by treatment with SHT + L. fermentum. Additionally, the potential hepatoprotective effect of fermented-SHTs correlated with the amount of unknown metabolite which is produced during fermentation process with L. fermentum, L.gasseri, or L.casei. Therefore, these results suggest that the hepatoprotective effect of SHT may be improved by fermentation with L. fermentum and the intestinal bacterial enzyme activities likely play an important role in the pharmacological action of herbal medicines.